Identifying Potential Solutions to Increase Discoverability and Reuse of Analog Datasets in Various Campus Locations. - Shannon L. Farrell; Julia Ann Kelly (Issues in Science and Technology Librarianship)
Describing, preserving, and providing access to data is now the purview of many science librarians, although the emphasis has been on data in electronic format. Data in paper or analog format might be found in many places around our campuses. At the University of Minnesota we conducted a preliminary investigation of analog data through discussions with faculty, staff, and the University Archives. We identified data in numerous locations, including the University Archives, personal collections, departmental holdings, museums, and off-campus research stations. We discovered data in many formats and carried out a few initial projects including creating a detailed inventory of one research center's analog data and digitizing and depositing one individual's dissertation data in our institutional repository. We also examined University Archives and discovered substantial amounts of analog data along with problems such as incomplete description or context. Overall we have identified several challenges and directions that we could take to make analog data more findable and available for reuse, but there is no clear single path forward. [ABSTRACT FROM AUTHOR]